2013
DOI: 10.1155/2013/408026
|View full text |Cite
|
Sign up to set email alerts
|

Germination Response of MR 219 Rice Variety to Different Exposure Times and Periods of 2450 MHz Microwave Frequency

Abstract: Germination is a key process in plants' phenological cycles. Accelerating this process could lead to improvment of the seedling growth as well as the cultivation efficiency. To achieve this, the effect of microwave frequency on the germination of rice seeds was examined. The physiological feedbacks of the MR 219 rice variety in terms of seed germination rate (GR), germination percentage (GP), and mean germination time (MGT) were analyzed by exposing its seeds to 2450 MHz of microwave frequency for one, four, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While the 2.45 GHz MWs radiation has no clear effect in seed germination, it seems to be beneficial on seedling growth and biomass accumulation in different species ( Aladjadjiyan, 2010 ; Jakubowski, 2010 ; Talei et al, 2013 ). As described for other types of radiation treatments, the effects of MWs on seeds depend on the plant species and growth stage, as well as, exposure duration, frequency, power density ( Jayasanka and Asaeda, 2014 ).…”
Section: Microwaves Potentialities In Seed Technologymentioning
confidence: 99%
“…While the 2.45 GHz MWs radiation has no clear effect in seed germination, it seems to be beneficial on seedling growth and biomass accumulation in different species ( Aladjadjiyan, 2010 ; Jakubowski, 2010 ; Talei et al, 2013 ). As described for other types of radiation treatments, the effects of MWs on seeds depend on the plant species and growth stage, as well as, exposure duration, frequency, power density ( Jayasanka and Asaeda, 2014 ).…”
Section: Microwaves Potentialities In Seed Technologymentioning
confidence: 99%
“…Azizi et al (2015) showed that two Malaysian cultivars, namely MARDI's Quality rice 74 (MRQ74) and MRQ50, also had the lowest number of callus induction from seed, proliferation and regeneration frequency. Among the four Malaysian upland rice cultivars, Kusan and Siam cultivars showed lowest response in terms of callus induction frequency and regeneration capability of the embryogenic callus (Shahsavari 2010 (Talei et al 2013). The cultivar has been considered as a high production rice with an appropriate quality in taste and shape, but sensitive to environmental changes (Panjaitan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…MR219 was derived between the MR137 and MR151 with maturation period of 105-111 days after sowing. This variety was released for the commercialization by the Malaysian Agricultural Research and Development Institute (MARDI) on the year of 2001 [29].…”
Section: Methodsmentioning
confidence: 99%